Dysfunctional Prefrontal Function Is Associated with Impulsivity in People with Internet Gaming Disorder during a Delay Discounting Task - Wang, Yifan; Hu, Yanbo; Xu, Jiaojing; Zhou, Hongli; Lin, Xiao; Du, Xiaoxia; Dong, Guangheng (Frontiers in Psychiatry, 2017)
Internet gaming disorder (IGD), defined as persistent use of online games with ignorance of adverse consequences, has increasingly raised widespread public concerns. The present study aimed at elucidating the precise mechanisms underlying IGD by comparing intertemporal decision-making process between 18 IGD participants and 21 matched healthy controls (HC). Both behavioral and fMRI data were recorded from a delay discounting task. At the behavioral level, the IGD showed a higher discount rate k than HC; and in IGD group, the reaction time (delay – immediate) and the discount rate k were both significantly positively correlated with the severity of IGD. At the neural level, the IGD exhibited reduced brain activations in the dorsolateral prefrontal cortex (DLPFC) and bilateral inferior frontal gyrus (IFG) as compared to HC during performing delay trials relative to immediate ones. Taken together, the results suggested that IGD showed deficits in making decisions and tended to pursuit immediate satisfaction. The underlying mechanism arises from the deficient ability in evaluating between delayed reward and immediate satisfaction, and the impaired ability in impulse inhibition, which may be associated with the dysfunction of the prefrontal activation. These might be the reason why IGD continue playing online games in spite of facing severe negative consequences.